Peculiarities Associated with the Adsorption of Inorganic and Organic Nitrogen-Containing Compounds on Amorphous Metal Surfaces - M.O. Kovbuz; O.M. Hertsyk; L.M. Bednars'ka (Adsorption Science & Technology)
The surface of an intermetallic amorphous alloy has a low density of localized energy centres which does not facilitate the adsorption of substances on the alloy surface. However, the active diffusion of amorphizators (usually B, Si) in these materials leads to their concentration on the surface. These amorphizators have a high affinity for organic compounds and can form non-covalent bonds with some of these compounds. Such behaviour has been observed for the adsorption of organic nitrogen-containing inhibitors on an iron-based amorphous alloy surface, although when the quantity of iron atoms is sufficient chemisorption with the formation of surface compounds of planar orientation is possible. The chemical bond is formed via the free electron pair associated with nitrogen, which results in a high activation energy (E a ) for the adsorption process. The adsorption of inorganic ions (Cl − , NO − 2 , NO − 3 ) increases as the iron content in the alloys increases (55–78.5%). This effect is most significant for the adsorption of chloride ions. The injection of piperidine, morpholine or diethylamine in a 3% sodium chloride solution results in significant changes in adsorption. In this case, it is believed that the adsorption mechanism changes leading to the formation of a two-layer adsorption film on the amorphous alloy surface.